Winery wastewater treatment for biomolecules recovery and water reuse purposes - Giacobbo, Alexandre (2023)
Winery wastewater has a high pollutant load, but it also contains added-value molecules, such as phenolic compounds, which can be recovered. The recovery of these biomolecules has aroused great interest, providing benefits under different aspects, such as valorization of byproducts recovered from wastewater; reduction of the pollutant load of winery wastewater, facilitating its treatment and reuse in agriculture; reducing the environmental impacts of wineries; and promotion of the circular economy, due to the recovery of biomolecules and water reuse. Based on these matters, the chapter focuses on bringing relevant aspects about the generation of wastewater throughout the winemaking process, indicating the main biomolecules of commercial interest present in the wastewater, and proposing processes for the recovery of these biomolecules. In addition, the main technologies that are used in the treatment of winery wastewater are reported and discussed, envisaging the reuse of treated wastewater in agriculture.